city and war - Grigoryeva, Elena; Lidin, Konstantin (project baikal, 2021)
And two thousand years of war. The war without any special cause. “The star called the Sun” (band Kino) Throughout its history, humanity has been fighting almost constantly. Cities were designed either as fortresses capable to hold the fort, or as permeable structures, which can be quickly restored after destruction. People, whose profession is meant for war, have always been a special caste and evoked a special attitude. We are witnessing an unprecedented process: the war changes its character, becomes undeclared, invisible, hybrid. How will a city, its appearance and functions respond to the new concepts of the war? How should we preserve, study and comprehend the military experience of the previous eras, the experience of educating “people of war” embodied in architecture of military schools? Not so long ago, historic Irkutsk lost the complex of Red Barracks related to the history of Port Arthur. The place is troubled again. While there is no problem with the building of the military school (the Ministry of Defense took it under their wing and is transforming it into the Suvorov School), there is a real war for preservation of exactly the same building of the cadet corps, which is fought in courts and public structures. As usual, we don’t try to take these issues off the table or to hide away from inconvenient topics, but start discussing them in a series of articles.